Pengaruh Perbedaan Jenis Larutan terhadap Hasil Praktikum Osmosis pada Kentang (Solanum tuberosum L.) dalam Pembelajaran Biologi - Yunisa Nadya Utami; Siti Khadijah; Vivin Alfiana (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2026)
Understanding osmosis through practical activities is essential for strengthening students' comprehension of membrane transport concepts in biology learning. This study aimed to examine the osmosis process in potatoes (Solanum tuberosum L.) by immersing potato samples in mineral water, salt solution, and sugar solution to determine how different solution concentrations influence water movement across cell membranes. A qualitative descriptive approach was employed through experimental activities and documentation. Potato samples were immersed in each solution for the same duration, and observations focused on changes in texture and physical condition following immersion. The results showed that potatoes immersed in mineral water became firmer due to water absorption, whereas samples immersed in salt and sugar solutions gradually lost firmness and exhibited shrinkage as water diffused out of the cells under hypertonic conditions. These findings demonstrate that differences in solution concentration directly influence osmotic water movement and provide practical evidence that supports the teaching of osmosis concepts in biology education.